LANGUAGE POLICIES IN THE FORMER COLONIZED COUNTRIES: A COMPARATIVE STUDY - Diyah Ayu Rizqiani (UAD TEFL International Conference)
Colonialism shapes the history of a country. The language policy of a former colonized country could be seen as a mirror to see the long history of colonialism. The colonizers have strong influence in establishing the education system and language instruction used at school. In this case, language as the important element in education system could be seen as manifestation of colonialism. The language instruction in the classroom is usually the official language of the country. Some former colonized countries proudly used English as academic language. On the other hand, there are other former colonized countries which use their indigenous language as the language instruction in the classroom. By comparing these two different language policies would also give different effects to their cultural and national identity. The aims of this paper are explaining the language policies, analyzing the effect of colonialism on education system, and describing the relation between language policy and nationalism.